Self-Created Film as a Resource in a Multimodal Conversational Narrative - Mascha Legel; Stijn R. J. M. Deckers; Gloria Soto; Nicola Grove; Annalu Waller; Hans van Balkom; Ronald Spanjers; Christopher S. Norrie; Bert Steenbergen (Multimodal Technologies and Interaction)
When access to natural speech is limited or challenging, as is the case for people with complex communication needs, self-created digital film can be practical to use as one of the resources within a multimodal conversation about a personal experience. The detailed and contextual information such audiovisual media offers with today’s available technology may assist the utility of other communication modes, such as (computerized) spoken, written or signed language, to foster mutual understanding and story growth. To promote the use of self-created film, here named a personal-video-scene (PVS), in the practice of augmentative and alternative communication (AAC), a greater understanding is required of how such media can operate as a resource within social interactions, such as daily conversations. This study therefore introduces a multimodal coding model developed to study the employment of a PVS within a film-elicited conversational narrative, relating to four aspects of conversational control: (a) topic development, (b) conversational structure, (c) conversational repair and (d) conversational maintenance. A case study illustrates how the use of a PVS in story-sharing was instrumental in establishing common ground between narrators, boosting the frequency of comments and questions, mitigating instances of conversational repair and expanding topic development.